The Relationship between Metacognitive Model and Metaemotion with Addiction Readiness the Mediating Role of Social Support among Adolescents - Arefe Mohamadnezhad; Niloofar Mikaeili (پژوهش‌های کاربردی روانشناختی)
The purpose was to investigateexamine the mediating role of social support in the relationship between the metacognitive model and metaemotion, as well as the propensity for addiction in adolescents. The statistical population of secondary school pupils in Shirvan city (N=1100) in 2020-2021, which was selected through online sampling, consisted of 200 individuals (109 boys and 91 girls). The correlational research method employed was structural equations. The Iranian Addiction Potential Scale (IAPS), Metacognitions Questionnaire (MCQ), Meta-Emotion Scale (MES), and Social Support Questionnaire (SSQ) were utilized as tools. The data were analyzed using SPSS 22 and Lisrel 8.8 software, which included mean and standard deviation and path analysis. Metacognitive beliefs and negative meta-excitement had a positive direct effect on addiction readiness, while meta-excitement and social support had a negative direct effect. Conversely, positive meta-excitement with social support had a positive direct effect. Through social support, 37 percent of metacognitive beliefs, 34 percent of positive emotions, and 35 percent of negative emotions indirectly influence readiness for addiction. Additionally, the model demonstrated a good fit. As a result, addiction is preceded by faulty metacognitive beliefs and negative meta-emotions, and the indirect impact of their social support on addiction preparation is discussed.